Analisis Analisis Perilaku Agresif Kelompok A Kota Pontianak - Dwi Sartika; Diana Diana; Yuniarti Yuniarti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study examines aggressive behavior in early childhood at Aisyiyah Bustanul Athfal 3 Pontianak. The study aimed to provide a comprehensive picture of the forms of aggressive behavior exhibited by group A children, analyze the handling strategies applied by teachers, and identify barriers in overcoming these behaviors. Using a qualitative approach with a case study method, data were collected through observation, interviews, and documentation. The research subjects were group A children at Aisyiyah Bustanul Athfal 3. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results showed that physical aggressive behavior was the most commonly observed form of aggression with a percentage of “Ever” occurrence of 17.11%. Verbal and relational aggression are also significant although not as high as physical aggression. The treatment strategies applied include behavioristic, cognitive, humanistic, and collaboration with parents. The research highlights the importance of the right approach in addressing aggressive behavior in early childhood. The main barriers include limited teacher understanding, inconsistency between school and home, and lack of parental support. Collaborative efforts from various parties are needed to effectively address these barriers.